Influence of UDP-glucuronosyltransferase polymorphisms on valproic acid pharmacokinetics in Chinese epilepsy patients - Chu, Xiao-Man; Zhang, Li-Fang; Wang, Guang-Ji; Zhang, Shen-Ning; Zhou, Jia-Hui; Hao, Hai-Ping (European journal of clinical pharmacology, 2012)
Purpose The aim of this study was to investigate the genetic polymorphisms of UGT1A3, UGT1A6, and UGT2B7 in Chinese epilepsy patients and their potential influence on the pharmacokinetics of valproic acid (VPA). Methods The genetic architectures of UGT1A3, UGT1A6, and UGT2B7 in 242 epilepsy patients were detected by DNA sequencing and PCR-restriction fragment length polymorphism. Steady-state plasma concentrations of VPA in 225 patients who had received VPA (approx. 250–1,000 mg/day) for at least 2 weeks were determined and associated with UGT polymorphisms. Results The allelic distribution of UGT1A3 in our Chinese epilepsy patients was significantly different from that in healthy subjects based on reference data. The standardized trough plasma concentration (C S ) of VPA was much lower in our patients with the UGT1A3*5 variant than in the wild type carriers (3.24 ± 1.05 vs. 4.68 ± 1.24 μg·kg·mL -1 ·mg -1 , P < 0.01). UGT polymorphisms had no influence on the pharmacokinetic interactions between carbamazepine and VPA. Conclusion Our results suggest that UGT1A3*5 may be an important determinant of individual variability in the pharmacokinetics of VPA and that it may be necessary to increase VPA dose for UGT1A3*5 carriers to ensure its therapeutic range of 50–100 μg/mL.